1985
DOI: 10.1021/bi00344a044
|View full text |Cite
|
Sign up to set email alerts
|

Yeast fatty acid synthase: structure to function relationship

Abstract: The yeast fatty acid synthase is a multifunctional enzyme composed of two nonidentical subunits in an alpha 6 beta 6 complex that is active in synthesizing fatty acids. The seven catalytic activities required for fatty acid synthesis are divided between the alpha and beta subunits such that the alpha 6 beta 6 complex has six complements of each activity. It has been proposed that these are organized into six centers for fatty acid synthesis. There are different opinions regarding the operation of these centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
34
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 13 publications
5
34
0
Order By: Relevance
“…Because the active sites are completely independent functionally (35), the biochemical data supported the fidelity of the symmetric model discussed above. At the same time, however, the data did not exclude the possibility of an asymmetric molecule, especially when we consider that FAS might exist in several thermodynamically stable states.…”
Section: Discussionsupporting
confidence: 57%
“…Because the active sites are completely independent functionally (35), the biochemical data supported the fidelity of the symmetric model discussed above. At the same time, however, the data did not exclude the possibility of an asymmetric molecule, especially when we consider that FAS might exist in several thermodynamically stable states.…”
Section: Discussionsupporting
confidence: 57%
“…However, the importance of double bonds in the cerulenin side chain is also proved for E. coli enzyme [16]. The main products of yeast FAS used in this experiment are palmitoyl-CoA and stearyl-CoA under the standard turnover conditions [33], although the formation of saturated fatty-acyl groups up to C24 has been reported under nonturnover conditions usingp-nitrophenyl thioacetate as an artificial substrate [34]. In the case of stearyl-CoA biosynthesis, intermediates which bind to the cysteine thiol of the condensing enzyme have c2-c16 acyl groups (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to the catalytic domains, almost half of the yeast FAS molecular mass is contributed by six structural domains, two in the α-subunit (SD1-2α) and four in the β-subunit (SD1-4β). Previous studies (15) have shown that the reaction chambers work independently of one another.…”
mentioning
confidence: 98%